2015
DOI: 10.1007/s11606-015-3452-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nephrologist Care on Management and Outcomes in Adults with Chronic Kidney Disease

Abstract: BACKGROUND: Predialysis nephrology care for adults with late stage chronic kidney disease (CKD) is associated with improved outcomes. Less is known about the effects of nephrology care in earlier stages of CKD. OBJECTIVE: We aimed to evaluate the effect of nephrology care on management of CKD risk factors and complications, CKD progression, incident cardiovascular disease (CVD), and death. DESIGN: This was a prospective cohort study. PARTICIPANTS: Participants included 3855 men and women aged 21 to 74 years en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 35 publications
(42 reference statements)
4
28
0
Order By: Relevance
“…15 Conversely, in a recent analysis of patients in the Chronic Renal Insufficiency Cohort study with a mean eGFR of 45 ml/min/1.73m 2 , nephrology care was neither associated with slower progression of CKD, nor with more frequent attainment of guideline concordant care. 16 Similarly, a study from the National Kidney Foundation–Kidney Early Evaluation Program (NKF-KEEP) found no association between nephrology care and mortality in patients with CKD. 17 A limitation of these prior studies is that they did not account for the trajectory of kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…15 Conversely, in a recent analysis of patients in the Chronic Renal Insufficiency Cohort study with a mean eGFR of 45 ml/min/1.73m 2 , nephrology care was neither associated with slower progression of CKD, nor with more frequent attainment of guideline concordant care. 16 Similarly, a study from the National Kidney Foundation–Kidney Early Evaluation Program (NKF-KEEP) found no association between nephrology care and mortality in patients with CKD. 17 A limitation of these prior studies is that they did not account for the trajectory of kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…Ricardo et al report that among patients with mild-moderate renal insufficiency, prior nephrology specialty care was associated with more frequent treatment of chronic kidney disease complications and use of medications affecting the renin-angiotensin axis but not with long-term outcomes. 4 This study should not be taken to invalidate Osler's adulation for Ban intimate knowledge of the varied aspects of disease.^A sturdy body of evidence in fact supports the premise that specialists (including both nephrologists and psychiatrists) are more likely than generalists to deliver guidelineconcordant care on a condition-by-condition basis. The article likely signals something more subtle.…”
mentioning
confidence: 81%
“…Numerous large clinical databases have been developed over the years that have allowed investigators to better understand the sociodemographic diversity associated with CKD development in adulthood. The Chronic Renal Insufficiency Cohort Study has published multiple articles (Ricardo et al 2015;Sandsmark et al 2015), and there are multiple excellent reviews available to better appreciate the relationships among risk factors for adult-onset CKD. Notably, the relationship between CKD and cardiovascular disease is complex and reciprocal.…”
Section: Life Course Health Development Origins Of Adolescent and Adumentioning
confidence: 99%